2012
DOI: 10.1016/j.jecp.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Learning what children know about space from looking at their hands: The added value of gesture in spatial communication

Abstract: This article examines two issues: the role of gesture in the communication of spatial information and the relation between communication and mental representation. Children (8–10 years) and adults walked through a space to learn the locations of six hidden toy animals and then explained the space to another person. In Study 1, older children and adults typically gestured when describing the space and rarely provided spatial information in speech without also providing the information in gesture. However, few 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 42 publications
6
40
1
1
Order By: Relevance
“…Moreover, the gestures that the participants produced conveyed the same information as was conveyed in the accompanying speech in all but 24 of the 239 trials (10%). The speech-gesture pattern in our study is thus different from many previous studies of spatial tasks, for example, Emmorey and Casey's (2001) study of adults telling another person where to place blocks, and Sauter and colleagues' (2012) study of children and adults telling another person about the layout of a simple space. Both groups found that the speaker often conveyed spatial information in gesture that was not found in the accompanying speech.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the gestures that the participants produced conveyed the same information as was conveyed in the accompanying speech in all but 24 of the 239 trials (10%). The speech-gesture pattern in our study is thus different from many previous studies of spatial tasks, for example, Emmorey and Casey's (2001) study of adults telling another person where to place blocks, and Sauter and colleagues' (2012) study of children and adults telling another person about the layout of a simple space. Both groups found that the speaker often conveyed spatial information in gesture that was not found in the accompanying speech.…”
Section: Discussioncontrasting
confidence: 99%
“…Gestures are on this account both an output from and an input to kinematic simulations. The results of previous studies in domains different from the formulation of algorithms are consistent with this account: during descriptions of spatial relations, iconic gestures reduce the need to describe referents (Chu & Kita, 2011;Sauter, Uttal, Alman, Goldin-Meadow, & Levine, 2012), and they help speakers to maintain information in memory (see, e.g., Morsella & Krauss, 2004;Wesp, Hess, Keutmann, & Wheaton, 2001). Studies have likewise shown that deictic gestures can improve memory for their referents (Petkov & Nikolova, 2010).…”
Section: Insert Figure 1 About Heresupporting
confidence: 55%
“…For example, Cooperrider et al (2016) found that when adults described abstract concepts of positive and negative feedback systems, they frequently used spatial relations only in their gestures. Similarly, Sauter, Uttal, Alman, Goldin‐Meadow, and Levine (2012) tested adults’ and 8‐ to 10‐year‐olds’ descriptions of object locations and found that participants revealed more about relative location through both their speech and gesture than through speech alone. These findings showed that gesture provides insights into the task‐specific spatial information that one explicitly produces and attends to, especially when verbalizing is difficult.…”
Section: Spatial Language and Spatial Cognitionmentioning
confidence: 99%